Hybrid films loaded with 5-fluorouracil and Reglan for synergistic treatment of colon cancer via asynchronous dual-drug delivery - Mao, Hairong; Zhou, Jianfeng; Yan, Liang; Zhang, Shuping; Yu, Deng-Guang (Frontiers in Bioengineering and Biotechnology, 2024)
Combined therapy with oral administration of several active ingredients is a popular clinic treatment on anticancer. However, the traditional way shows poor convenience and less safety and efficiency to the patients. The combination of traditional pharmaceutical technique and the advanced materials conversion methods is able to provide new solutions to solve this issue. In this research, a new kind of hybrid films were created through a coaxial electrospraying and a followed casting process. The films were composed of reglan and 5-fluorouracil (5-FU)-loaded cellulose acetate (CA) core-shell particles within the polyvinylpyrrolidone (PVP) film matrix. The microscopic observations demonstrated that the films had a solid cross-section with the loaded core-shell particles. X-ray diffraction and Fourier Transform Infra-Red tests verified that the loaded reglan and 5-FU presented in the films in an amorphous state and showed fine compatibility with the polymeric matrices, i.e. PVP and CA, respectively. In vitro dissolution tests indicated that the films were able to provide the desired asynchronous dual-drug delivery, a fast release of reglan and a followed sustained release of 5-FU. The controlled release mechanisms of an erosion mechanism for reglan and a typical Fickian diffusion mechanism for 5-FU were disclosed. The protocols reported here pioneered a new way for fabricating multiple drugs loaded biomaterials with each has its own controlled release behaviors for a synergistic anticancer treatment.